Design Thinking for Entrepreneurs and Small Businesses Putting the Power of Design to Work - Ingle, Beverly Rudkin. (Apress : Imprint: Apress, 2013)
Having met Beverly Ingle and hearing her speak about design thinking, I was enlightened and enthused. With a depth of knowledge and obvious passion for the usage of design thinking, she has already helped many business people, myself included, inject greater creativity into problem solving to deliver better results—something that is a must for left-brainers! She has an amazingly refreshing ability to create deep understanding within her audience, and a hands-on, practical approach ensures that the results are manageable and within your grasp.   —Jill Robb, CEO, Ambition Digital; Belfast, United Kingdom Design Thinking for Entrepreneurs and Small Businesses: Putting the Power of Design to Work is the first book on the subject for smaller businesses. Until now, design thinking—a methodology for solving business problems and identifying opportunities—has been the playground for companies with big budgets, giving them the advantage of the innovation that comes from using the latest design thinking tools emerging from Stanford, Harvard, Northwestern, and elsewhere. Now, thanks to design thinking expert Beverly Ingle, entrepreneurs and small-business owners can make the design thinking playground their own—and on a much smaller budget. Ingle provides the tools entrepreneurs need as well as step-by-step processes that show how to use design thinking methods to transform your business and drive organizational success. Design Thinking for Entrepreneurs and Small Businesses offers just enough theory to provide you with working knowledge of design thinking, but its value lies in the practical, proven, hands-on information that you can put to use immediately. You will learn: How to incorporate design thinking processes into everyday operations, and in what areas of business the approach is most valuable  How to use the most prevalent and popular design thinking tools (like ideation, prototyping, and rapid branding) effectively How to use design thinking to identify and achieve your business goals and create new business models How to create revenue-boosting new products and services using design thinking How to improve the customer/user experience to create more loyal, profitable customers By the time you've finished reading the last chapter of Design Thinking for Entrepreneurs and Small Businesses, you will not just be thinking about producing new products and services, boosting customer service, or developing new business opportunities—you'll be doing it. Best, it’ll show up in the top and bottom lines.      .